Scrum in a business development organization : Case study from the financial sector - Währn, Marika (My University, 2019)
Context – Organizations are transforming ways of working to different agile methodologies to answer to the never-ending change and growing demand from customers. The different agile methodologies aim to speed the development of products and services by iterative development that is open and welcomes change. Objective – As agile has been used in software and IT development for longer time, this study investigates how business development organizations use the scrum framework. The overall ways scrum framework is used in business development organization is researched by using a framework created based on scrum theory and strategy as practice theory. Method – The empirical part of the thesis was conducted as a single case study in a company that is operating in the financial sector. Nine semi-structured interviews were conducted and those were analysed as three different cases based on the role of the interviewee. Results and discussion – It was seen that scrum framework can be used in a business development organization, as long as there is the freedom to adjust it based on the requirements of a team. This study provides a model for studying the different practices and praxis of scrum aspects regardless of industry.
Keywords: agile, scrum, strategy as practice, practice theory, business development; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development